The Influence of the PhET Virtual Lab Assisted PBL Model on Energy Transformation Material on the Learning Motivation of Elementary School Students - Tiza Ariesta Saputri; Ana Fitrotun Nisa; Akbar Al Masjid; Banun Havifah Cahyo Khosiyono (Postgraduate, University of Mataram, 2025)
The challenge faced in basic education is how to present learning materials so that they are interesting, relevant, and able to encourage students to be motivated to learn actively. This study aims to find out whether there is a difference and influence of the PhET Virtual Lab Assisted PBL Model on Energy Transformation Material on the Learning Motivation of SDN Triharjo State Elementary School Students. The methodology adopted is a Quantitative approach quasi-experimental. The analysis use normality test, homogeneity of variance test, independent sample, and paired sample t test. The results of the study that sig. independent sample test 0.00 < 0.05 (there’s different with applying the PhET Virtual Lab of 44.09 and not applying the PhET Virtual Lab of 37.73) and sig. paired sample t test (H0 is rejected). So, the PBL Model assisted by PhET Virtual Lab has a significant influence on students motivation which is higher compared to the PBL Model without the assistance of PhET Virtual Lab of Triharjo State Elementary School Students.